23 GHz VLBI observations of SN 2008ax - Marti-Vidal, I.; Marcaide, J.; Alberdi, A.; Guirado, J.; Prez-Torres, M.; Ros, E.; Shapiro, I.; Beswick, R.; Muxlow, T.; Pedlar, A.; Argo, Megan (EDP Sciences, 2009)
We report on phase-referenced 23 GHz Very-Long-Baseline-Interferometry (VLBI) observations of the type IIb supernova SN 2008ax,made with the Very Long Baseline Array (VLBA) on 2 April 2008 (33 days after explosion). These observations resulted in a marginal detection of the supernova. The total flux density recovered from our VLBI image is 0.8 0.3 mJy (one standard deviation). As it appears, the structure may be interpreted as either a core-jet or a double source. However, the supernova structure could be somewhat confused with a possible close by noise peak. In such a case, the recovered flux density would decrease to 0.480.12 mJy, compatible with the flux densities measured with the VLA at epochs close in time to our VLBI observations. The lowest average expansion velocities derived from our observations are (1.90±0.30) 105 km s-1 (case of a double source) and (5.2±1.3) 104 km s-1 (takingthe weaker source component as a spurious, close by, noise peak, which is the more likely interpretation). These velocities are 7.3 and 2 times higher, respectively, than the maximum ejecta velocity inferred from optical-line observations.